Contrasting contributions of surface hydrological pathways in convection permitting and parameterised climate simulations over Africa and their feedbacks on the atmosphere - Sonja S. Folwell; Christopher M. Taylor; Rachel A. Stratton (Climate Dynamics, 2022)
The partitioning of rainfall at the land surface into interception, infiltration and surface runoff plays an important role in the water cycle as it controls the time scale at which water returns to the atmosphere. Rainfall intensity is of crucial importance to this partition. High resolution convection permitting models significantly improve simulated sub-daily rainfall intensity distributions, in particular those associated with convective rainfall in the tropics. Here we compare the land surface hydrological response in a pair of 10-year simulations over an African domain performed using the Met Office Unified Model: a typical configuration using parameterised convection operating at 25 km and the second a high resolution convection permitting simulation at 4.5 km with the parametrized convection switched off. Overall pan-African interception in the convection permitting scheme is 70% lower, whilst surface runoff is 43% higher than the parameterized convection model. These changes are driven by less frequent, but more intense rainfall with a 25% increase in rainfall above 20 mm h −1 in the 4.5 km model. The parameterised scheme has a ~ 50% canopy water contribution to evaporative fraction which is negligible in the convection permitting scheme. Conversely, the convection permitting scheme has higher throughfall and infiltration leading to higher soil moisture in the weeks following rain resulting in a 30–50% decrease in the daytime sensible heat flux. We examine how important the sub-grid rainfall parameterisation in the model is for the differences between the two configurations. We show how, switching a convective parameterisation off can substantially impact land surface behaviour.

Improved climatological precipitation characteristics over West Africa at convection-permitting scales - Ségolène Berthou; David P. Rowell; Elizabeth J. Kendon; Malcolm J. Roberts; Rachel A. Stratton; Julia A. Crook; Catherine Wilcox (Climate Dynamics, 2019)